Efficacy of nystatin for the treatment of oral candidiasis: a systematic review and meta-analysis - Lyu X; Zhao C; Yan ZM; Hua H (Dove Medical Press, 2016)
Xin Lyu, Chen Zhao, Zhi-min Yan, Hong HuaDepartment of Oral Medicine, Peking University School and Hospital of Stomatology, Beijing, People’s Republic of ChinaObjective: To systematically review and assess the efficacy, different treatment protocols (formulation, dosage, and duration), and safety of nystatin for treating oral candidiasis.Methods: Four electronic databases were searched for trials published in English till July 1, 2015. Randomized controlled trials comparing nystatin with other antifungal therapies or a placebo were included. Clinical and/or mycological cure was the outcome evaluation. A meta-analysis or descriptive study on the efficacy, treatment protocols, and safety of nystatin was conducted.Results: The meta-analysis showed that nystatin pastille was significantly superior to placebo in treating denture stomatitis. Nystatin suspension was not superior to fluconazole in treating oral candidiasis in infants, children, or HIV/AIDS patients. The descriptive investigations showed that administration of nystatin suspension and pastilles in combination for 2 weeks might achieve a higher clinical and mycological cure rate, and using the nystatin pastilles alone might have a higher mycological cure rate, when compared with using nystatin suspensions alone. Nystatin pastilles at a dose of 400,000 IU resulted in a significantly higher mycological cure rate than that administrated at a dose of 200,000 IU. Furthermore, treatment with nystatin pastilles for 4 weeks seemed to have better clinical efficacy than treatment for 2 weeks. Descriptive safety assessment showed that poor taste and gastrointestinal adverse reaction are the most common adverse effects of nystatin.Conclusion: Nystatin pastille was significantly superior to placebo in treating denture stomatitis, while nystatin suspension was not superior to fluconazole in treating oral candidiasis in infants, children, or HIV/AIDS patients. Indirect evidence from a descriptive study demonstrated that administration of nystatin pastille alone or pastille and suspension in combination is more effective than that of suspension alone; prolonged treatment duration for up to 4 weeks can increase the efficacy of nystatin. More well designed and high quality randomized control studies are needed to confirm these findings.Keywords: nystatin, oral candidiasis, systematic review, meta-analysis, safety, dosage forms, treatment duration